# Bessel polynomials

(Redirected from Bessel polynomial)

In mathematics, the Bessel polynomials are an orthogonal sequence of polynomials. There are a number of different but closely related definitions. The definition favored by mathematicians is given by the series (Krall & Frink, 1948)

${\displaystyle y_{n}(x)=\sum _{k=0}^{n}{\frac {(n+k)!}{(n-k)!k!}}\,\left({\frac {x}{2}}\right)^{k}}$

Another definition, favored by electrical engineers, is sometimes known as the reverse Bessel polynomials (See Grosswald 1978, Berg 2000).

${\displaystyle \theta _{n}(x)=x^{n}\,y_{n}(1/x)=\sum _{k=0}^{n}{\frac {(n+k)!}{(n-k)!k!}}\,{\frac {x^{n-k}}{2^{k}}}}$

The coefficients of the second definition are the same as the first but in reverse order. For example, the third-degree Bessel polynomial is

${\displaystyle y_{3}(x)=15x^{3}+15x^{2}+6x+1\,}$

while the third-degree reverse Bessel polynomial is

${\displaystyle \theta _{3}(x)=x^{3}+6x^{2}+15x+15\,}$

The reverse Bessel polynomial is used in the design of Bessel electronic filters.

## Properties

### Definition in terms of Bessel functions

The Bessel polynomial may also be defined using Bessel functions from which the polynomial draws its name.

${\displaystyle y_{n}(x)=\,x^{n}\theta _{n}(1/x)\,}$
${\displaystyle y_{n}(x)={\sqrt {\frac {2}{\pi x}}}\,e^{1/x}K_{n+{\frac {1}{2}}}(1/x)}$
${\displaystyle \theta _{n}(x)={\sqrt {\frac {2}{\pi }}}\,x^{n+1/2}e^{x}K_{n+{\frac {1}{2}}}(x)}$

where Kn(x) is a modified Bessel function of the second kind, yn(x) is the ordinary polynomial, and θn(x) is the reverse polynomial (pg 7 and 34 Grosswald 1978). For example:[1]

${\displaystyle y_{3}(x)=15x^{3}+15x^{2}+6x+1={\sqrt {\frac {2}{\pi x}}}\,e^{1/x}K_{3+{\frac {1}{2}}}(1/x)}$

### Definition as a hypergeometric function

The Bessel polynomial may also be defined as a confluent hypergeometric function (Dita, 2006)

${\displaystyle y_{n}(x)=\,_{2}F_{0}(-n,n+1;;-x/2)=\left({\frac {2}{x}}\right)^{-n}U\left(-n,-2n,{\frac {2}{x}}\right)=\left({\frac {2}{x}}\right)^{n+1}U\left(n+1,2n+2,{\frac {2}{x}}\right).}$

The reverse Bessel polynomial may be defined as a generalized Laguerre polynomial:

${\displaystyle \theta _{n}(x)={\frac {n!}{(-2)^{n}}}\,L_{n}^{-2n-1}(2x)}$

from which it follows that it may also be defined as a hypergeometric function:

${\displaystyle \theta _{n}(x)={\frac {(-2n)_{n}}{(-2)^{n}}}\,\,_{1}F_{1}(-n;-2n;-2x)}$

where (−2n)n is the Pochhammer symbol (rising factorial).

The inversion for monomials is given by

${\displaystyle {\frac {(2x)^{n}}{n!}}=(-1)^{n}\sum _{j=0}^{n}{\frac {n+1}{j+1}}{j+1 \choose n-j}L_{j}^{-2j-1}(2x)={\frac {2^{n}}{n!}}\sum _{i=0}^{n}i!(2i+1){2n+1 \choose n-i}x^{i}L_{i}^{(-2i-1)}\left({\frac {1}{x}}\right).}$

### Generating function

The Bessel polynomials, with index shifted, have the generating function

${\displaystyle \sum _{n=0}^{\infty }{\sqrt {\frac {2}{\pi }}}x^{n+{\frac {1}{2}}}e^{x}K_{n-{\frac {1}{2}}}(x){\frac {t^{n}}{n!}}=1+x\sum _{n=1}^{\infty }\theta _{n-1}(x){\frac {t^{n}}{n!}}=e^{x(1-{\sqrt {1-2t}})}.}$

Differentiating with respect to ${\displaystyle t}$, cancelling ${\displaystyle x}$, yields the generating function for the polynomials ${\displaystyle \{\theta _{n}\}_{n\geq 0}}$

${\displaystyle \sum _{n=0}^{\infty }\theta _{n}(x){\frac {t^{n}}{n!}}={\frac {1}{\sqrt {1-2t}}}e^{x(1-{\sqrt {1-2t}})}.}$

### Recursion

The Bessel polynomial may also be defined by a recursion formula:

${\displaystyle y_{0}(x)=1\,}$
${\displaystyle y_{1}(x)=x+1\,}$
${\displaystyle y_{n}(x)=(2n\!-\!1)x\,y_{n-1}(x)+y_{n-2}(x)\,}$

and

${\displaystyle \theta _{0}(x)=1\,}$
${\displaystyle \theta _{1}(x)=x+1\,}$
${\displaystyle \theta _{n}(x)=(2n\!-\!1)\theta _{n-1}(x)+x^{2}\theta _{n-2}(x)\,}$

### Differential equation

The Bessel polynomial obeys the following differential equation:

${\displaystyle x^{2}{\frac {d^{2}y_{n}(x)}{dx^{2}}}+2(x\!+\!1){\frac {dy_{n}(x)}{dx}}-n(n+1)y_{n}(x)=0}$

and

${\displaystyle x{\frac {d^{2}\theta _{n}(x)}{dx^{2}}}-2(x\!+\!n){\frac {d\theta _{n}(x)}{dx}}+2n\,\theta _{n}(x)=0}$

## Generalization

### Explicit Form

A generalization of the Bessel polynomials have been suggested in literature (Krall, Fink), as following:

${\displaystyle y_{n}(x;\alpha ,\beta ):=(-1)^{n}n!\left({\frac {x}{\beta }}\right)^{n}L_{n}^{(1-2n-\alpha )}\left({\frac {\beta }{x}}\right),}$

the corresponding reverse polynomials are

${\displaystyle \theta _{n}(x;\alpha ,\beta ):={\frac {n!}{(-\beta )^{n}}}L_{n}^{(1-2n-\alpha )}(\beta x)=x^{n}y_{n}\left({\frac {1}{x}};\alpha ,\beta \right).}$

For the weighting function

${\displaystyle \rho (x;\alpha ,\beta ):=\,_{1}F_{1}\left(1,\alpha -1,-{\frac {\beta }{x}}\right)}$

they are orthogonal, for the relation

${\displaystyle 0=\oint _{c}\rho (x;\alpha ,\beta )y_{n}(x;\alpha ,\beta )y_{m}(x;\alpha ,\beta )\mathrm {d} x}$

holds for mn and c a curve surrounding the 0 point.

They specialize to the Bessel polynomials for α = β = 2, in which situation ρ(x) = exp(−2 / x).

### Rodrigues formula for Bessel polynomials

The Rodrigues formula for the Bessel polynomials as particular solutions of the above differential equation is :

${\displaystyle B_{n}^{(\alpha ,\beta )}(x)={\frac {a_{n}^{(\alpha ,\beta )}}{x^{\alpha }e^{-{\frac {\beta }{x}}}}}\left({\frac {d}{dx}}\right)^{n}(x^{\alpha +2n}e^{-{\frac {\beta }{x}}})}$

where a(α, β)
n
are normalization coefficients.

### Associated Bessel polynomials

According to this generalization we have the following generalized differential equation for associated Bessel polynomials:

${\displaystyle x^{2}{\frac {d^{2}B_{n,m}^{(\alpha ,\beta )}(x)}{dx^{2}}}+[(\alpha +2)x+\beta ]{\frac {dB_{n,m}^{(\alpha ,\beta )}(x)}{dx}}-\left[n(\alpha +n+1)+{\frac {m\beta }{x}}\right]B_{n,m}^{(\alpha ,\beta )}(x)=0}$

where ${\displaystyle 0\leq m\leq n}$. The solutions are,

${\displaystyle B_{n,m}^{(\alpha ,\beta )}(x)={\frac {a_{n,m}^{(\alpha ,\beta )}}{x^{\alpha +m}e^{-{\frac {\beta }{x}}}}}\left({\frac {d}{dx}}\right)^{n-m}(x^{\alpha +2n}e^{-{\frac {\beta }{x}}})}$

## Particular values

{\displaystyle {\begin{aligned}y_{0}(x)&=1\\y_{1}(x)&=x+1\\y_{2}(x)&=3x^{2}+3x+1\\y_{3}(x)&=15x^{3}+15x^{2}+6x+1\\y_{4}(x)&=105x^{4}+105x^{3}+45x^{2}+10x+1\\y_{5}(x)&=945x^{5}+945x^{4}+420x^{3}+105x^{2}+15x+1\end{aligned}}}

none of which factor. Filaseta and Trifonov (Journal for Pure and Applied Mathematics, 550:125-140, 2002) proved that all Bessel polynomials are irreducible.

Resulting in the following reverse bessel polynomials:

{\displaystyle {\begin{aligned}\theta _{1}(x)&=1\\\theta _{1}(x)&=x+1\\\theta _{2}(x)&=x^{2}+3x+3\\\theta _{3}(x)&=x^{3}+6x^{2}+15x+15\\\theta _{4}(x)&=x^{4}+10x^{3}+45x^{2}+105x+105\\\theta _{5}(x)&=x^{5}+15x^{4}+105x^{3}+420x^{2}+945x+945\\\end{aligned}}}